S6P mutation in Delta and Omicron variant spike protein significantly enhances the efficacy of mRNA COVID-19 vaccines - Bong, Yong-Sik; Brown, David; Chung, Ezra; Ananthaswamy, Neeti; Chen, Renxiang; Lewoczko, Evan; Sabbers, William; Patterson-Orazem, Athéna C.; Dorsey, Zachary; Zou, Yiqing; Yu, Xue; Liang, Jiening; et al. (Frontiers in Immunology, 2025)
BackgroundThe unrelenting emergence of SARS-CoV-2 variants has significantly challenged the efficacy of existing COVID-19 vaccines. Enhancing the stability and immunogenicity of the spike protein is critical for improving vaccine performance and addressing variant-driven immune evasion.MethodsWe developed an mRNA-based vaccine, RV-1730, encoding the Delta variant spike protein with the S6P mutation to enhance stability and immunogenicity. The vaccine’s immunogenicity and protective efficacy were evaluated in preclinical models, including monovalent (RV-1730) and bivalent (RV-1731) formulations targeting the Delta and BA.1 variants. Additionally, the effectiveness of RV-1730 as a heterologous booster following primary vaccination with BNT162b2 (Pfizer-BioNTech) and mRNA-1273 (Moderna-NIAID) was assessed.ResultsRV-1730 elicited significantly stronger B and T cell responses and more durable neutralizing antibodies compared to S2P-based vaccines. The bivalent RV-1731 vaccine demonstrated broad neutralizing activity against emerging variants, including XBB1.5 and JN.1. Importantly, RV-1730, when used as a heterologous booster following initial immunization with BNT162b2 or mRNA-1273, significantly enhanced neutralizing antibody titers against multiple variants, including Delta and Omicron. Both RV-1730 and RV-1731 provided superior protection in preclinical models, indicating enhanced efficacy due to the S6P mutation.ConclusionThe incorporation of the S6P mutation into the Delta variant spike protein significantly enhances the immunogenicity and efficacy of mRNA-based COVID-19 vaccines. The strong performance of RV-1730 as a heterologous booster and the broad-spectrum activity of the bivalent RV-1731 vaccine underscore their potential as versatile and effective vaccination strategies against SARS-CoV-2 and its evolving variants.